Homophobia: An Impulsive Attraction to the Same Sex? Evidence From Eye-Tracking Data in a Picture-Viewing Task. Issue 5 (1st May 2016) - Cheval, Boris; Radel, Remi; Grob, Emmanuelle; Ghisletta, Paolo; Bianchi-Demicheli, Francesco; Chanal, Julien
ABSTRACT: Introduction: Some models suggest that homophobia can be explained as a denied attraction toward same-sex individuals. While it has been found that homophobic men have same-sex attraction, these results are not consistent. Aim: This study drew on the dual-process models to test the assumption that sexual interest in homosexual cues among men high in homophobia will depend on their specific impulses toward homosexual-related stimuli. Methods: Heterosexual men ( N = 38) first completed a scale measuring their level of homonegativity. Then, they performed a manikin task to evaluate their impulsive approach tendencies toward homosexual stimuli (IAHS). Main outcomes measures: A picture-viewing task was performed with simultaneous eye-tracking recording to assess participants' viewing time of the visual area of interest (i.e., face and body). Results: IAHS positively predicted the viewing time of homosexual photographs among men with a high score of homonegativity. Men with a high homonegativity score looked significantly longer at homosexual than at heterosexual photographs but only when they had a high IAHS. Conclusion: These findings confirm the importance of considering the variability in impulsive processes to understand why some (but not all) men high in homophobia have homosexual interest. These findings reinforce the theoretical basis for elaborating a dual-process model for behaviors in the sexual context.